Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/iai.73.11.7281-7289.2005
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Innate Immunity toCampylobacter jejuniResults in Induction of Bactericidal Human Beta-Defensins 2 and 3

Abstract: Campylobacter jejuni is the most prevalent cause of bacterial diarrhea worldwide. Despite the serious health problems caused by this bacterium, human innate immune responses to C. jejuni infection remain poorly defined. Human ␤-defensins, a family of epithelial antimicrobial peptides, are a major component of host innate defense at the gastrointestinal mucosal surface. In this study, the effect of two different C. jejuni wild-type strains on human intestinal epithelial innate responses was investigated. Up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 40 publications
4
64
2
1
Order By: Relevance
“…It was demonstrated that probiotics enhance secretion of β-defensin (BD) (Delcenserie et al 2008), however in our study only separate β-defensin positive connective tissue and inflammation cells were observed. Although in a healthy colon β-defensin 2 (BD2) and β-defensin 3 (BD3) are absent, low levels of BD2 and BD3 induction may result in a defective antimicrobial barrier function at the mucosal surface (Zilbauer et al 2005). Our finding about a positive relation between enteric pathogens and intensity of defensin expression in intestine cells of pigs testifies to the stimulating role of defensin on cell proliferation as a compensatory mechanism that agrees with findings of other researchers (Zilbauer et al 2005, Schlee et al 2008.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It was demonstrated that probiotics enhance secretion of β-defensin (BD) (Delcenserie et al 2008), however in our study only separate β-defensin positive connective tissue and inflammation cells were observed. Although in a healthy colon β-defensin 2 (BD2) and β-defensin 3 (BD3) are absent, low levels of BD2 and BD3 induction may result in a defective antimicrobial barrier function at the mucosal surface (Zilbauer et al 2005). Our finding about a positive relation between enteric pathogens and intensity of defensin expression in intestine cells of pigs testifies to the stimulating role of defensin on cell proliferation as a compensatory mechanism that agrees with findings of other researchers (Zilbauer et al 2005, Schlee et al 2008.…”
Section: Discussionsupporting
confidence: 81%
“…Although in a healthy colon β-defensin 2 (BD2) and β-defensin 3 (BD3) are absent, low levels of BD2 and BD3 induction may result in a defective antimicrobial barrier function at the mucosal surface (Zilbauer et al 2005). Our finding about a positive relation between enteric pathogens and intensity of defensin expression in intestine cells of pigs testifies to the stimulating role of defensin on cell proliferation as a compensatory mechanism that agrees with findings of other researchers (Zilbauer et al 2005, Schlee et al 2008. With confirmation of authors (Veldhuizen et al 2008) that porcine BD2 was active against both gram-positive and gram-negative bacteria in vitro, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that decreased levels or malfunctioning of defensins in the intestine might lead to disturbance of this homeostasis resulting in intestinal diseases such as Crohn's disease and ulcerative colitis in human (Wehkamp et al, 2005a,b). Furthermore, an upregulation of intestinal defensins is observed as an early response to bacterial infections of the intestine (Zilbauer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Different from the Paneth cell restricted HD5 and HD6, with which they share their small size and cationic character, b-defensins are present in a variety of epithelial cells, including enterocytes. While the human b-defensin (HBD) 1 (also known by its gene name DEFB101) is constitutively expressed, others, like HBD2 (gene name DEFB4) show pathogen and/or inflammation dependent upregulation Ogushi et al, 2001a;Zilbauer et al, 2005Zilbauer et al, , 2010 while also being inducible by probiotic bacteria (Schlee et al, 2007(Schlee et al, , 2008. Interestingly, HBDs are genetically clustered in a copy-number (CN) or gene dosage variable region with a diploid number of up to 12.…”
Section: Gut Defensinsmentioning
confidence: 99%